1878 Va. Acts 301, Carrying Concealed Weapons, ch. VI, § 7 - (:unkn) unknown (My University, 1877)
If a person habitually carry about his person, hid from common observation, any pistol, dirk, bowie-knife, or any weapon of the like kind, he shall be fined not more than fifty dollars.
Keywords: CARRY - CONCEALED